2015
DOI: 10.1016/j.semcdb.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

R3 receptor tyrosine phosphatases: Conserved regulators of receptor tyrosine kinase signaling and tubular organ development

Abstract: Summary R3 receptor tyrosine phosphatases (RPTPs) are characterized by extracellular domains composed solely of long chains of fibronectin type III repeats, and by the presence of a single phosphatase domain. There are five proteins in mammals with this structure, two in Drosophila, and one in Caenorhabditis elegans. R3 RPTPs are selective regulators of receptor tyrosine kinase (RTK) signaling, and a number of different RTKs have been shown to be direct targets for their phosphatase activities. Genetic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…Earlier studies in Drosophila epithelial tissues and mammalian cells showed that Ptp4E and Ptp10D dampen RTK signalling 5,9,49 . Btk29A, on the other hand, is a positive RTK effector 13,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies in Drosophila epithelial tissues and mammalian cells showed that Ptp4E and Ptp10D dampen RTK signalling 5,9,49 . Btk29A, on the other hand, is a positive RTK effector 13,15 .…”
Section: Discussionmentioning
confidence: 99%
“…It involves two type III receptor protein tyrosine phosphatases (PTPs), Ptp10D and Ptp4E, the non-receptor tyrosine kinase (non-RTK) Btk29A, and the actin nucleation-promoting factor WASH (Wiskott–Aldrich syndrome protein and SCAR homologue). Type III PTPs contain a single catalytic phosphatase domain in the cytoplasmic region and fibronectin type III-like domains in their extracellular region 5,6 . In Drosophila , Ptp10D and Ptp4E 7 control airway tube shapes through negative regulation of epidermal growth factor receptor (EGFR) signalling 8 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that they dephosphorylate tyrosine kinases (RTK) to regulate RTK signaling since most of the known substrates of R3 RPTPs are RTKs [14, 16]. An involvement of these proteins and R3 RPTPs from invertebrate model animals, except PTP52F, in tubular organ development, has been suggested by Jeon and Zinn, 2015 [14].…”
Section: Discussionmentioning
confidence: 99%
“…The specific involvement of vertebrate R3 RPTPs in cancer and other pathologies has been the subject of several recent reports and reviews [ 1 , 4 , 12 , 13 ]. In invertebrates, R3 RPTPs have been functionally characterized in protostome animal models: PTP52F, PTP10D and PTP4e in the fruitfly Drosophila melanogaster and F44G4.8/DEP-1 (nematode.2 sequence in this study) in the nematode Caenorhabditis elegans (reviewed by Jeon and Zinn, 2015) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soady et al showed that PTPRB negatively regulates branching morphogenesis in the mammary epithelium, dependent on inhibition of FGFR activation and ERK1/2 phosphorylation 9 . Genetic studies in both mammals and invertebrate model systems have shown that the RPTP family is essential for tubular organ development 10 .…”
Section: Introductionmentioning
confidence: 99%